Compositional compartmentalization and compositional patterns in the nuclear genomes of plants. - Salinas, J (1988)
We report here results which indicate (i) that the nuclear genomes of angiosperms is characterized by a compositional compartmentalization and an isochore structure; and (ii) that the nuclear genomes of some Gramineae exhibit strikingly different compositional patterns compared to those of many dicots. Indeed, the compositional distribution of nuclear DNA molecules (in the 50-100 Kb size range) from three dicots (pea, sunflower and tobacco) and three monocots (maize, rice and wheat) were found to be centered around lower (41%) and higher (45% for rice, 48% for maize and wheat) GC levels, respectively (and to trail towards even higher GC values in maize and wheat). Experiments on gene localization in density gradient fractions showed a remarkable compositional homogeneity in vast (greater than 100-200 Kb) regions surrounding the genes. On the other hand, the compositional distribution of coding sequences (GenBank and literature data) from dicots (several orders) was found to be narrow, symmetrical and centered around 46% GC, that from monocots (essentially barley, maize and wheat) to be broad, asymmetrical and characterized by an upward trend towards high GC values, with the majority of sequences between 60 and 70% GC. Introns exhibited a similar compositional distribution, but lower GC levels, compared to exons from the same genes.